The use of nanoencapsulation to decrease human skin irritation caused by capsaicinoids - Contri RV (Dove Medical Press, 2014)
Renata V Contri,1 Luiza A Frank,2 Moacir Kaiser,1 Adriana R Pohlmann,1,3 Silvia S Guterres1,2 1Programa de Pós-Graduação em Ciências Farmacêuticas, 2Faculdade de Farmácia, 3Instituto de Química, Universidade Federal do Rio Grande do Sul, Porto Alegre, Rio Grande do Sul, Brazil Abstract: Capsaicin, a topical analgesic used in the treatment of chronic pain, has irritant properties that frequently interrupt its use. In this work, the effect of nanoencapsulation of the main capsaicinoids (capsaicin and dihydrocapsaicin) on skin irritation was tested in humans. Skin tolerance of a novel vehicle composed of chitosan hydrogel containing nonloaded nanocapsules (CH-NC) was also evaluated. The chitosan hydrogel containing nanoencapsulated capsaicinoids (CH-NC-CP) did not cause skin irritation, as measured by an erythema probe and on a visual scale, while a formulation containing free capsaicinoids (chitosan gel with hydroalcoholic solution [CH-ET-CP]) and a commercially available capsaicinoids formulation caused skin irritation. Thirty-one percent of volunteers reported slight irritation one hour after application of CH-NC-CP, while moderate (46% [CH-ET-CP] and 23% [commercial product]) and severe (8% [CH-ET-CP] and 69% [commercial product]) irritation were described for the formulations containing free capsaicinoids. When CH-NC was applied to the skin, erythema was not observed and only 8% of volunteers felt slight irritation, which demonstrates the utility of the novel vehicle. A complementary in vitro skin permeation study showed that permeation of capsaicinoids through an epidermal human membrane was reduced but not prevented by nanoencapsulation. Keywords: chitosan, nanocapsules, capsaicinoids, skin irritation, skin permeation